New Stamps - Kenya Government Second Issue - Kenya, Government of Kenya Postal Service (African Businesd, 1980)
KENYA: Flying doctor service. Set of stamps issued as a tribute to the fine work done by the Flying doctor service. Values 50 cents, 1/-, 3/-, 5/-. Issued March 20, 1990 (Crown Agents)
Kenya - Flying Doctor Service
Keywords: Flying Doctor Service; Stamps; Postal